Avaliação da incidência de Aflatoxina, Fumonisina e Zearalenona em milho produzido entre 2016 e 2018 nos estados de Paraná, Mato Grosso e Mato Grosso do Sul - Mistura, Marcelo (2019)
Brazil is currently the 3rd largest producer of corn, most of which are 70%, it is intended to produce feed for animal feed. Studies point, however, that 25% of all cereals produced in the world are contaminated with some type of mycotoxin, with corn being the cereal most susceptible to the effects caused by the attack of fungi that, under stress conditions such as variations in temperature, humidity, exposure to luminosity and availability of nutrients can develop mycotoxins. Mycotoxins are understood as natural biological substances produced from the secondary metabolization of some types of filamentous fungi. Each mycotoxin has a certain pathogenic effect on the infected individual, but in general promote lower absorption of nutrients causing damage to kidneys, liver and lungs, and can still interfere in the reproductive system. The main mycotoxins found in corn are Aflatoxin (AFL), Fumonisin (FUM) and Zearalenona (ZEA). The objective of this work was to evaluate the contamination and incidence of mycotoxins present in corn in the main producing states in Brazil throughout the 2015/16, 2016/17 and 2017/18 seasons by mapping mycotoxin contamination in these states relating the impact that temperature stress conditions and precipitation have on the data found of mycotoxins. Were found results below the quantification limit (ALQ) for 83.33% of AFL, 15.92% of FUM and 53.03% of ZEA, while 3.50% of AFL, 48.84% of FUM and 10.26% of ZEA samples had results above the maximum value (AVM) allowed by legislation. Because it presented developmental characteristics at lower temperatures and suffer less from external effects, the concentrations and incidence of ZEA have reduced over the sampled period. The state that was highlighted in relation to the data was Paraná, where it had the highest incidences and higher concentration of this mycotoxin. In general, 55.93% of the samples analyzed in Paraná had positive results for the presence of ZEA, with an index of 15.85% of the samples with results greater than 400 µg kg-1. The data of the reduction of ZEA are extremely related to the reduction of indexes and better distribution of accumulated precipitation. The concentrations of AFLs and FUMs have distinct characteristics of ZEA. Since these are produced by fungi that have the development characteristic in the post-harvest, the data show that they did not have the gradual reduction, but the concentrations generally had a small reduction between the first and last evaluation period, but with an increase in the second period. The mean concentration of FUMs reduced 60.35%, and 83.74% of the samples presented FUM contamination, and 48.84% of the total had results above 5000 µg kg-1, this demonstrates that in the period there was a reduction in incidence with reduction in concentration. Contamination by AFLs decreased by 30.63% in the mean results, with a reduction of 51.12% incidence, 3.50% of samples with a concentration above 50 µg kg-1. The state of Mato Grosso (MT) had the highest incidence and average concentration of AFLs, especially for the months between September and December 2016, where the highest concentration obtained was 824 µg kg-1 of AFLs. External precipitation and temperature factors may have contributed to these results, but as the development characteristics of AFLs is postharvest, the storage factor seems to play the largest role in the high concentrations of mycotoxin. As expected, external factors such as temperature, precipitation and storage seem to be the biggest interference in the production of mycotoxins in corn.